Geography of India - Husain,Majid (. - Chennai, 2020)
1.Geological structure and formation of India structure of India -- 2.Physiography -- 3.The drainage system of India -- 4.Climate of India -- 5.Natural vegetation and National parks -- 6.Soils -- 7.Resources -- 8.Energy resources -- 9.Agriculture -- 10.Spatial organization of agriculture -- 11.Industries -- 12.Transport, communications and trade -- 13.Cultural setting -- 14.Settlements -- 15.Regional development and planning -- 16.India-political aspects -- 17.Contemporary Issues.